RELIGIOUS AWARENESS BASED ON SOCIO-CULTURAL GEOGRAPHY OF MTSN STUDENTS IN BANTEN - Nuriah, Siti; Dartina, Vina; Rayagginansih, Syari Fitrah; Abdulrahman, Triyantini R.; Fahriza, Irfan (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2025)
Juvenile delinquency, intolerance and disciplinary behaviour are partly motivated by low religious awareness. State MTs students in Banten have urban and traditional socio-cultural diversity, while geographically consisting of rural, urban, mountainous, and coastal areas. This diversity affects the cultivation of values, traditions, and perspectives on their religious life. The research aims to describe the religious awareness of MTs students in the Banten Region based on their socio-cultural and geographical profiles.  The research method used is descriptive analysis, using Analysis of Variance (ANOVA). Research data were obtained using a religious awareness scale that measured cognitive, affective, and psychomotor aspects. The ANOVA test results show that sociocultural factors have a more significant impact on the variation of religious awareness of MTs Negeri students in the Banten Region. Socio-culturally, religious awareness tends to be greater for students in urban sociocultural groups.